The Impact of Product Quality and Brand Image on Repurchase Intention Through Customer Satisfaction - Mulyaningsih, Putri; Meria, Lista (Pandawan, 2024)
The importance of repurchasing intention indicates a product's success or failure in the market. This study aimed to determine and analyze the effect of product quality and brand image on repurchase intention through consumer satisfaction with Scarlett Whitening products. The data processing method in this study used the Structural Equation Modeling (SEM) modeling equation with a total of 135 respondents. This study uses a quantitative analysis approach that adopts Partial Least Square (PLS). This study uses inferential statistical data analysis. The first finding is that product quality positively affects customer satisfaction. The brand image on customer satisfaction is declared influential or accepted. Product quality has a positive effect on repurchase intention and is accepted. The effect of brand image on repurchase intention is declared to have no effect, or the hypothesis is proven to be rejected. Customer satisfaction has a positive effect on repurchase intention. The results empirically prove if product quality affects repurchase intention, mediated by consumer satisfaction. Brand image has a positive effect on repurchase intention mediated by consumer satisfaction. This study has implications for management that a good brand image of Scarlett body lotion will generate fame or can be said to attract consumers' attention, and quality Scarlett body lotion products will also increase consumer repurchases.